Adaptação de prótese auditiva em sujeitos com perda auditiva unilateral - Dalla Costa, Lidiéli (2018)
This research aimed to investigate the speech recognition in silence and in noise of subjects presenting unilateral hearing loss, without and with a hearing aid and to analyze the benefit, self-perception of the functional performance, satisfaction and the use of hearing aid in these subjects. Were evaluated 11 adults, presenting unilateral hearing loss, mixed or sensorineural type, from mild to severe degrees. The speech recognition was assessed using the Sentence Lists test in Brazilian Portuguese; the functional performance of the hearing was evaluated through the Speech Spatial and Qualities of Hearing Scale questionnaire; the satisfaction through the Satisfaction with Amplification in Daily Life, both in Brazilian Portuguese; and to evaluate the use of the hearing aid was analyzed the report of the patient. The hearing aid adaptation provided a speech recognition benefit in all evaluated positions, in silence and in noise. The subjects did not mention great limitations in the activities of communication during the use of the hearing aid. They were satisfied with the use of sound amplification. Most of the subjects do not make effective use of hearing aid. The discontinuation of the use can be justified by the difficulty of perceiving the restriction of participation caused by hearing loss, as well as the benefit of the prosthesis, besides the concern with the costs with the batteries and aesthetic aspects. Despite presenting benefit in speech recognition in silence and in noise and satisfaction with hearing aid, most subjects with unilateral hearing loss do not make effective use of the hearing aid.